BANGUNAN SEKOLAH LUAR BIASA BAGIAN B DI JAKARTA DENGAN PENDEKATAN DEAFSPACE GUIDELINES - Ester Oktafiani; Galuh Widati; Riyadi Ismanto (UKI Press, 2022)
A deaf person is a person who has hearing loss. Consequently, they cannot hear sounds and voices perfectly. Such causes them to have difficulties communicating so that many of them lose their opportunity to excel. Nonetheless their intelligence level is the same as other normal children. Hence with the limitations they have, they need to be treated specifically. Special School Part B will provide opportunities for deaf children to obtain decent education and develop their respective potentials. By applying the concepts of deaf space, space and distance, sensory range, mobility and proximity, lighting and color, and acoustics, the designed school can meet the needs of deaf children. With the particular educational facilities, deaf children can be united in the same surroundings, so that they will feel pleasant when learning and interact with each other. Thus they can cultivate self-confidence and are no longer underrated by society.